Pengaruh Notam Latihan Militer Terhadap Pelayanan Pemanduan Lalu Lintas Penerbangan di Perum LPPNPI Cabang Pembantu Curug - Fatmawati Sari; RB Budi Kartika W Wilatikta; Susi Suhardianti (Politeknik Penerbangan Indonesia Curug, 2021)
The purpose of this research to know the effect NOTAM military exercise in air traffic control service at Perum LPPNPI sub-branch Curug. The method used in this research is quantitative research and data collected used questionnare. As for the population in this research are Air Traffic Controller personnels and pilot students 4 and 69 of PPIC. The result shows negative effect and opposite between NOTAM military exercise and air traffic control service. Negative effect shows increasing NOTAM military exercise so air traffic control service will be distrubed. Determination coefficient is 47,61% and the rest is determined by the other factors. The regression equation test is Y = 40,526 – 0,619X.